KEMAMPUAN VISUAL THINKING DALAM TRANSLASI REPRESENTASI MATERI PERBANDINGAN TRIGONOMETRI SISWA SMA NEGERI 5 PONTIANAK - Yaniartini, Yaniartini; Hartoyo, Agung; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the ability of visual thinking in the translation of representation of students who have high, medium and low mathematical abilities for trigonometric comparison material in XI IPA SMA Negeri 5 Pontianak. The research method used in this research is descriptive method. The research subjects were 9 students from class XI IPA 1. The subjects of this study were determined based on students' mathematical grades and the consideration of mathematics teachers. The results of data analysis show that students with high mathematical abilities already have visual thinking abilities in translational representation, whereas students with moderate and low mathematical abilities do not yet have these abilities. Students with high mathematical ability have been able to meet all indicators of visual thinking ability in translational representation, while students with moderate mathematical ability have not been able to meet the indicators showing & telling and students with low mathematical ability have not been able to meet the indicators of imagining and showing & telling. Overall, the ability to visual thinking in the translation of representation of students XI IPA SMA Negeri 5 Pontianak is still relatively low. Keywords: Visual Thinking Ability, Translation of Representasion